1970
DOI: 10.1085/jgp.56.4.421
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Description of the Dynamics of Excitation and Inhibition in the Eye of Limulus

Abstract: By means of intracellular microelectrode techniques, we have measured the dynamics of the several processes which translate light stimulation into spike activity in the Limulus eye. The transductions from light to voltage and from voltage to spike rate, and the lateral inhibitory transduction from spike rate to voltage, we have characterized by transfer functions. We have checked the appropriateness of treating the eye as a system of linear transducers under our experimental conditions. The response of the eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 17 publications
(21 reference statements)
4
88
0
Order By: Relevance
“…Furthermore, similar work has been presented for both retinular and eccentric cells in Limulu (Knight, Dodge & Toyoda, 1970;Dodge, Knight & Toyoda, 1968;Pinter, 1966) and locust and cricket (Pinter, 1972).…”
Section: Introductionsupporting
confidence: 55%
“…Furthermore, similar work has been presented for both retinular and eccentric cells in Limulu (Knight, Dodge & Toyoda, 1970;Dodge, Knight & Toyoda, 1968;Pinter, 1966) and locust and cricket (Pinter, 1972).…”
Section: Introductionsupporting
confidence: 55%
“…Stimulus presentation and control were identical to those described by Knight et al (1970). The stimulus waveform was generated by adding together constant voltages with time-varying voltages generated by a waveform generator (Hewlett-Packard 3300A).…”
Section: Stimulus and Stimulus Controlmentioning
confidence: 99%
“…The important mechanism to understand, in connection with this problem, is the process which produces the impulse rate from depolarization. Knight et al (1970) have shown that this process acts like a linear transducer for small modulated signals; in other words, it can be characterized by its frequency response, S(f). S(f) is defined as the relative modulation (peak to peak divided by the average) of the impulse rate divided by the relative modulation of the driving current at the frequency f.…”
Section: Frequency Response Of the Current-to-firing Rate Processmentioning
confidence: 99%
See 1 more Smart Citation
“…An early system-analytic study of the crayfish stretch-receptor by Borsellino, Poppele, and Terzuolo [7] has led to a comparative study by Fohlmeister, Poppele and Purple [16,17] of nerve-impulse generating transducers. The linear frequency response of the lateral eye of the horseshoe crab Limulus was given early investigation by Pinter [40], by Biederman-Thorson and Thorson [5,52], and by Dodge, Knight and Toyoda [14,26,43], Over the past decade a very detailed and predictively accurate linear system-analytic model has evolved for the visual neurophysiology of Limulus [8,9,44], There now have been a substantial number of experimental forays unto applying methods of nonlinear system identification, in the general spirit of Wiener's proposal, to biological transducers [15, 19, 20, 28, 30, 32, 33, 35-37, 45, 46, 53, 55, 57], Concurrently, the theoretical state of the subject has continued to advance. It was recognized before 1963 by Barrett [2] that Wiener's white-noise approach is just one member of a wide class of analytic procedures, each based on its own particular ensemble of input test signals.…”
Section: Introductionmentioning
confidence: 99%